2016
DOI: 10.1016/j.supflu.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical water oxidation (SCWO) for the removal of N-containing heterocyclic hydrocarbon wastes. Part I: Process enhancement by addition of isopropyl alcohol

Abstract: The present work investigates the destruction of nitrogencontaining heterocyclic hydrocarbons frequently encountered in hazardous wastes by supercritical water oxidation (SCWO), with focus on the process enhancement using isopropyl alcohol (IPA) as co-fuel. 1,8-Diazabicyclo [5.4.0] undec-7-ene (DBU) was selected for SCWO in a continuous plug flow reactor, under a range of temperatures (400-525 °C), oxidant ratios nSR (0.8-2.0) and IPA/DBU ratios (0.5-3.5). Experimental results were presented in terms of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…IPA addition showed some influence on TOC % removal at various temperatures. In effect, this agrees with the experimental results of Part I [16], which showed that IPA addition had a minor influence on TOC % removal. Figure 3 shows the analysis of data to evaluate k 0 and E a .…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…IPA addition showed some influence on TOC % removal at various temperatures. In effect, this agrees with the experimental results of Part I [16], which showed that IPA addition had a minor influence on TOC % removal. Figure 3 shows the analysis of data to evaluate k 0 and E a .…”
Section: Figuresupporting
confidence: 91%
“…The experimental apparatus designed and constructed at the University of Birmingham (UK), was detailed in previous work [16]. It comprises a 12m plug-flow SS316 reactor of 1/16" diameter (0.6mm ID) and 3.07mL volume.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…DiNaro et al [10] investigated the SCWO of benzene at temperature ranging from 479 • C to 587 • C with initial benzene concentration from 0.4 to 1.2 mmol/L. Complete conversion of benzene with stoichiometric oxygen at 246 bar was achieved only when the temperature was higher than 575 • C. Pinto et al [11] conducted a series of SCWO experiments on quinoline with the concentration of about 0.3mmol/L, indicating that 100% TOC removal was not achieved until the temperature approached 650 • C. Also the research on DBU(1,8-diazabicyclo [5.4.0]undec-7-ene) by Al-Duri et al [12] has shown that temperature is the main factor enhancing the oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Density and dielectric constant of water beyond the critical point decrease, and this in turn determines high solubility of a huge group of non-polar compounds in water, including gases and organic compounds. At the same time the loss of polarity causes that compounds with an ionic structure practically do not dissolve in it any longer [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%